EFEK ANTIFERTILITAS EKSTRAK AIR BIJI PEPAYA (Carica papaya L.)TERHADAP JUMLAH DAN DIAMETER FOLIKEL de Graaf MENCIT (Mus musculus) BETINA - Muhamad Adnan Jafar Alfian; Agung Janika Sitasiwi; Muhammad Anwar Djaelani (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2018)
Papaya seed (Carica papaya L.) is known to be used as an herbal contraceptive. Papaya seeds contain anti-fertility compounds that can suppress fertility by interfering the ovarian function. The aim of this research was to find out the antifertility effect of papaya seed extract (Carica papaya L.) to the number and diameter of the Graafian follicle in female mice (Mus musculus). This research was conducted using Complete Randomized Design (CRD). Laboratory animals were treated with K(-) (Control with solvent); K(+) (Control with the contraceptive pill); P1, P2, and P3 (Treatment with doses of 1.4 mg, 3.5 mg, and 7 mg papaya seed, respectively, for each individual). The treatment was conducted for 21 days. The observed parameters were ovarian weight; body weight; number, diameter, and theca thickness of Graafian follicle. Data processing was performed using ANOVA test and tested further by Duncan test. All analyses were performed with a significance level of 5% (a = 0.05). Data were analyzed using SPSS version 16.0 computer program. The results showed that papaya seed extract was not significantly different (p> 0,05) on ovarium weight, body weight, Graafian follicle diameter, and theca layer thickness but significantly different (p <0,05) on the number of Graafian follicles in female mice. The conclusion of this research is the papaya seeds extracted by water can decrease the number of Graafian follicle so potentially to be used as an antifertility of female mice. Keywords: Antifertility, Papaya Seeds, Graafian follicle, Mus musculus